IMPLEMENTATION OF THE REGULATION OF THE MINISTER OF MANPOWER OF THE REPUBLIC OF INDONESIA NUMBER 39 OF 2016 CONCERNING ONLINE JOB SEEKER CARD (AK-1) SERVICES AT THE MANPOWER OFFICE OF LANGKAT REGENCY - Anton Prasetio; Adam; Heri Kusmanto (International Journal of Cultural and Social Science, 2026)
The implementation of technology-based public service policies represents one of the government’s strategic efforts to enhance the quality and effectiveness of public service delivery. One such policy is the Regulation of the Minister of Manpower of the Republic of Indonesia Number 39 of 2016 concerning Manpower Placement, which regulates the online issuance of the Job Seeker Card (AK-1). This study aims to analyze the implementation of the policy on online Job Seeker Card (AK-1) services at the Manpower Office of Langkat Regency and to identify the supporting and inhibiting factors affecting its implementation. This research employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observation, and documentation. The analysis of policy implementation refers to George C. Edward III (1980) model, which includes communication, resources, disposition, and bureaucratic structure [4]. The findings indicate that the implementation of the online AK-1 service policy has been carried out in accordance with the applicable regulations. However, the implementation has not yet reached an optimal level. The main challenges include limited human resources, technical system disruptions, low levels of digital literacy among certain segments of the community, and suboptimal bureaucratic coordination. Therefore, strengthening institutional capacity, improving information technology infrastructure, and enhancing policy socialization are necessary to ensure more effective and efficient service delivery.